2021
DOI: 10.1016/j.reth.2021.07.001
|View full text |Cite
|
Sign up to set email alerts
|

Cultured epithelial autografts for the treatment of large-to-giant congenital melanocytic nevus in 31 patients

Abstract: Introduction Giant congenital melanocytic nevus (GCMN) is a large melanocytic nevus, and its full-thickness removal is usually difficult due to the lack of skin available for reconstruction. Curettage is an alternative approach in cases of GCMN to remove the superficial dermis above the cleavage plane with a curette in the neonatal period, and its major complications include repigmentation, retarded epithelization, and hypertrophic scar formation. In Japan, the JACE® cultured epidermal autograft (… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 19 publications
0
5
0
Order By: Relevance
“…Whether all patients with CMN should undergo brain MRI remains an open question. A positive result on MRI for NCM may impact decisions regarding timing and extent of surgical management for CMN, because brain MRI can suggest whether NCM is stable or progressive and indications for aggressive treatment of CMN will be considered based on the prognosis of NCM 31 . Patients with NCM may be asymptomatic, but occasionally present with headache associated with hydrocephalus, seizure, mental retardation, and various abnormalities of the CNS, including Dandy–Walker syndrome, Chiari malformation, syringomyelia, and lissencephaly 7 , 15 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…Whether all patients with CMN should undergo brain MRI remains an open question. A positive result on MRI for NCM may impact decisions regarding timing and extent of surgical management for CMN, because brain MRI can suggest whether NCM is stable or progressive and indications for aggressive treatment of CMN will be considered based on the prognosis of NCM 31 . Patients with NCM may be asymptomatic, but occasionally present with headache associated with hydrocephalus, seizure, mental retardation, and various abnormalities of the CNS, including Dandy–Walker syndrome, Chiari malformation, syringomyelia, and lissencephaly 7 , 15 , 32 .…”
Section: Discussionmentioning
confidence: 99%
“…This study also reported a mean take rate of 68% for CEA, while STSG had a take rate of 84%. 46 In a 2021 study by Morimoto et al, 48 31 patients with GCMN were treated with CEA after curettage of the lesions. Cultured epithelial autograft significantly affected the speed and efficiency of wound healing, when compared with patients who did not receive CEA after curettage, demonstrating that CEAs can accelerate epithelialization in such wounds.…”
Section: Cultured Epithelial Autografts As a Treatment For Congenital...mentioning
confidence: 99%
“…Clinical studies showed that CEA could be an effective option to accelerate epithelization after curettage or ablation of CMN. 74,76,77 However, the low take rate compared with conventional grafting techniques and the vulnerability of skin produced from CEA cannot be ignored. Moreover, the high financial cost and the demand for nursing resources have limited the wide applicability of CEA.…”
Section: Surgerymentioning
confidence: 99%
“…In theory, CEA can provide one‐stage wound coverage, thereby reducing the number of surgeries. Clinical studies showed that CEA could be an effective option to accelerate epithelization after curettage or ablation of CMN 74,76,77 . However, the low take rate compared with conventional grafting techniques and the vulnerability of skin produced from CEA cannot be ignored.…”
Section: Treatments For Cmnmentioning
confidence: 99%